Pengaruh Information Quality, Social Psychological Distance, Sense of Power dan Trust terhadap Consumer Purchase Intentions pada Social Commerce (Studi Kasus: TikTok) - Yosse, Fernando; Wuisan, Dewi S. S. (Sam Ratulangi University, 2021)
This study aims to see the effect of information, social psychological distance, a sense of power & trust on consumer purchase intentions on TikTok social commerce. TikTok social media company is a relatively new company among other social media companies, to create a good social trading environment, TikTok's steps are quite good in implementing various social trading features in it, one of which is the inclusion of links in the bio of social media profiles. However, the company is also expected to pay attention to the platform from several variables, namely information quality, social psychological distance, sense of power, trust and purchase intention. This study uses individual primary data methods using questionnaires as a medium to obtain data from respondents. In this study, researchers took respondents who were Indonesian citizens. The total respondents in this study were probably 1055 respondents. This research uses data processing with Partial Least Square - Structural Equation Modeling (PL-SEM) and is processed using SmartPLS software. The results obtained in this study indicate that electronic word of mouth has a positive and significant effect on the response of TikTok social media users, so that users will make purchase intentions mediated by trust.